From the Guest Editor… Special Issue on Graph-Based Representations - Horvitz, Eric (Journal of Decision Analysis, 2005)
Graphical representations have played a central role in decision analysis. Although decision trees remain popular, more general graphical languages can be used to encode relationships among variables of a decision basis. Influence diagrams, introduced in the late 1970s, provide a general graphical representation for decision analysis. We publish, in this first of two volumes of a special issue of Decision Analysis, the original manuscript on influence diagrams, along with a retrospective by the authors. We also include two new articles focusing respectively on the use of graphical models for group coordination challenges and on handling the unintended side effects of interventions.